New insights, perspectives and strategies in phytotechnologies - Othman, Rashidi (Nova Science Publishers, Inc., 2024)
The use of any living organisms under Plantae Kingdom to accumulate, sequester, remediate or degrade inorganic and organic pollutants in air, soil, or water are called Phytotechnologies. Phytotechnology makes use of engineering, science, and living organisms as living technology to address ecological issues This chapter is designed to provide the reader with new insights, perspectives and strategies in phytotechnologies. Due to the wide range of Plantae living organism classifications, different applications of phytotechnologies such as the implementation of halophytes, pteridophytes, bryophytes, microphytes and macrophytes are covered in this book. The basic plant mechanisms including chelation and sequestration via various ligands that regulate the uptake and accumulation of both essential and non-essential heavy metals are also provided. Therefore, the valuable information in this book may serve as reference material for researchers, stakeholders, ecologists, landscape architects, agriculturists, horticulturists, and professionals working on all aspects related to plants and ecosystems. Finally, different phytotechnology techniques are designed, implemented and applied to accommodate a different site's unique characteristics or site-specific considerations using different types of living organisms as phytotechnology agents.